Cauliflower-shaped ZnO nanomaterials for electrochemical sensing and photocatalytic applications. (20th December 2016) - Ibrahim, Ahmed A.; Kumar, Rajesh; Umar, Ahmad; Kim, S.H.; Bumajdad, Ali; Ansari, Z.A.; Baskoutas, S.
Abstract: This paper reports a facile, low-temperature solution growth, characterization, photocatalytic and sensing applications of ZnO cauliflowers. The prepared ZnO cauliflowers were characterized by various techniques in order to confirm their morphological, structural, compositional and optical properties. Electrochemical sensing application of as-synthesized ZnO nanomaterials was studied against picric acid, a harmful, toxic and explosive nitrophenol. A reproducible and reliable sensitivity of 24.14 μA.mM −1 cm −2 and experimental detection limit of 0.078 mM with the correlation coefficient (R 2 ) of 0.97829 and good linearity from 0.078 mM to 10.0 mM was observed using ZnO cauliflower based chemical sensor. Further, the ZnO cauliflowers were applied as a photocatalyst for the degradation of methylene blue dye. Almost complete dye degradation was observed within 90 min of UV light irradiation. The sensing and photocatalytic mechanisms for ZnO nanomaterials with cauliflower morphologies have also been studied. Langmuir–Hinshelwood model revealed a first order kinetic for dye photodegradation with synthesized material. The present study confirmed that the ZnO nanomaterials with cauliflower morphology could be a potential candidate as a photocatalyst for dye degradation and an efficient electron mediator for sensing applications.